Implementation of Cooperative Models Jigsaw with the Assignment of Mind Map to Improve the Mastery of Concepts and Creative Thinking Abilities of Students - Lilis Sulistiawati; Siti Sriyati (Universitas Sebelas Maret, 2015)
This study aimed to analyze the differences mastery of concepts and creative thinking skills among students who get through the implementation of cooperative models jigsaw with the assignment mind map and students who get through the implementation of the conventional model with assignment mind map. The method used is a quasi-experimental research design with pre test-post test control group Design. The sampling technique is done by cluster random sampling of 60 students consisting of 30 students control class and 30 students experimental class. Data collected through preliminary tests (pretest) and final test (posttest) mastery of concepts and creative thinking abilities of students. Data analysis used Mann Whitney test. Based on the results of data analysis, found the results of the first study, there were significant differences between the experimental class concept mastery and control classes (sig = 0,000 < α = 0.05), the significance of the differences between the students' ability to think creatively experimental class and control class (0.039 < α = 0.05). The conclusion was that the use of a model cooperative jigsaw with the assignment mind map better than the use of conventional models with the assignment mind map.Keywords: Jigsaw, Mind Map, Mastery of Concepts, Creative Thinking.